2007
DOI: 10.1681/asn.2006050459
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Endothelial Nitric Oxide Synthase Knockout Mice Develop Advanced Diabetic Nephropathy

Abstract: The pathogenesis of diabetic nephropathy remains poorly defined, and animal models that represent the human disease have been lacking. It was demonstrated recently that the severe endothelial dysfunction that accompanies a diabetic state may cause an uncoupling of the vascular endothelial growth factor (VEGF)-endothelial nitric oxide (eNO) axis, resulting in increased levels of VEGF and excessive endothelial cell proliferation. It was hypothesized further that VEGF-NO uncoupling could be a major contributory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
347
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 343 publications
(380 citation statements)
references
References 48 publications
25
347
1
5
Order By: Relevance
“…53 This last possibility seems unlikely, however, given that thrombomodulin is associated with the endothelial marker CD34 in eNOSKO mice. 24 Last of all, IHC was used to assess the levels of soluble factors such as PDGF. This may not be the most reliable method, because of secretion of these molecules; other strategies, such as glomerular isolation, should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…53 This last possibility seems unlikely, however, given that thrombomodulin is associated with the endothelial marker CD34 in eNOSKO mice. 24 Last of all, IHC was used to assess the levels of soluble factors such as PDGF. This may not be the most reliable method, because of secretion of these molecules; other strategies, such as glomerular isolation, should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Renal histology was examined at 4 months with blood and urine collected to measure blood urea nitrogen and urinary albumin/creatinine ratio, as described previously. 24 The scheme of the experimental design is presented in Figure 1.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Streptozotocin (STZ), which induces hyperglycemia by selectively damaging pancreatic b cells, has been administered to genetically modified rodents to create a variety of DN models. [3][4][5][6] The validity of one of these models, the diabetic (mREN-2)27 rat, has been questioned because of the apparent overwhelming impact of its genetically mediated hypertension on renal pathology. 7 One group of investigators reported that STZ-induced diabetes in female heterozygous (mREN-2)27 rats recapitulates the proteinuria, nodular glomerulosclerosis, and progressive loss of renal function that are cardinal features of DN in human beings.…”
mentioning
confidence: 99%